Glycans as regulatory elements of the insulin/IGF system: Impact in cancer progression - Freitas-Junior, JCM (2017)
The insulin/insulin-like growth factor (IGF) system in mammals comprises a dynamic network of proteins that modulate several biological processes such as development, cell growth, metabolism, and aging. Dysregulation of the insulin/IGF system has major implications for several pathological conditions such as diabetes and cancer. Metabolic changes also culminate in aberrant glycosylation, which has been highlighted as a hallmark of cancer. Changes in glycosylation regulate every pathophysiological step of cancer progression including tumour cell-cell dissociation, cell migration, cell signaling and metastasis. This review discusses how the insulin/IGF system integrates with glycosylation alterations and impacts on cell behaviour, metabolism and drug resistance in cancer.